Existence, Uniqueness, and Approximation for Solutions of a Functional-integral Equation in Lp Spaces - Afonso, S. M. [UNESP]; Azevedo, J. S.; Da Silva, M. P. G.; Rocha, A. M. (Sociedade Brasileira de Matemática Aplicada e Computacional, 2019)
In this work we consider the general functional-integral equation:y(t)=f(t,âˆ«01k(t,s)g(s,y(s))ds),tâˆˆ[0,1], and give conditions that guarantee existence and uniqueness of solution in Lp([0,1]), with 1 1pâˆ.We use Banach Fixed Point Theorem and employ the successive approximation method and Chebyshev quadrature for approximating the values of integrals. Finally, to illustrate the results of this work, we provide some numerical examples.

Neste trabalho estabelecemos condiÃ§Ãµes que garantem existÃªncia e unicidade de soluÃ§Ã£o da equaÃ§Ã£o integral-funcional geral y(t)=f(t,âˆ«01k(t,s)g(s,y(s))ds),tâˆˆ[0,1], em Lp([0,1]), com 1pâˆ. Utilizamos o Teorema de Ponto Fixo de Banach e aplicamos o mÃ©todo de aproximaÃ§Ãµes sucessivas e a quadratura de Chebyshev para aproximar os valores das integrais. Finalmente, para ilustrar os resultados obtidos no trabalho, fornecemos alguns exemplos numÃ©ricos.
Keywords: functional-integral equations; Lp spaces; existence; uniqueness; successive approximation; equações integrais-funcionais; espaços Lp; existência; unicidade; aproximações sucessivas